Biocoating of concrete - Bannavong, Moukdavanh (2016)
Concrete structures near an offshore area that expose to the marine environment are the most vulnerable to concrete deterioration due to the presence of water, oxygen, and aggressive minerals. Treatment of concrete surface can be a solution to strengthen the serviceability of concrete. Recently, researchers are investigating on an environmental friendly approach using urease producing bacteria to induce calcium carbonate precipitation on the concrete surface which function as a protective layer called "microbial-induced calcite precipitate" (MICP). The performance of MICP is considerably dependent on the amount of calcium carbonate precipitation that deposits on the concrete surface. This research study aims to investigate the effectiveness of MICP using two types of bacteria such as urease producing bacteria (UPB) and enrichment culture by three methods of applying MICP, spray, brush, and immersion methods. Besides, sodium silicate is used with UPB to increase adhering rate of the bacteria on the concrete surface to lengthen the exposure time between bacteria culture and the cementitious solution. The performance of calcium carbonate precipitation by both spray and brush methods are almost identical while immersion method is completely different. The immersion method resulted in a higher amount of calcium carbonate precipitation than other methods. The experimental results show that the amount of water absorption by immersion method was reduced by about 2.7% and 2.3% as compared to a control and other methods respectively. As a result, the concrete treated by immersion method has a better performance regarding water uptake resistance. Hence, the most efficient approach to applying MICP on concrete is by immersion.